Da Rio de Janeiro a Medellin: la nascita della teologia post-conciliare latinoamericana - Campagnaro, Matteo (Warszawskie Studia Teologiczne, 2021)
In recent decades, from a theological point of view, the Church in Latin America has gone from being a "receiving" church to being a "protagonist" church. This happened thanks to the dynamic development of a new way of practicing theology. Latin American post-Conciliar theology presents a new existential, kerygmatic and methodological approach based on a wise balance (hermeneutic circle) between orthopraxis and orthodoxy. The article presents and attempts to critically analyze the most important events of the period from the first Latin American Episcopal Conference in Rio de Janeiro in 1955 to the second in Medellin in 1968, which laid the foundations for the birth of post-Conciliar Latin America theology: the rise of CELAM, the choice of John XXIII, the Cuban Revolution and the Vatican Council II and especially the Constitution Gaudium et Spes, which introduces a new theological paradigm that recognizes the historical realities of pluralism of nations and cultures, as well as social, political and economic structures. Undoubtedly, the election of Cardinal Bergoglio as Pope is a "sign of the times" that makes the richness and freshness of Latin American theological reflection powerfully join the world theological discourse.